2021
DOI: 10.1109/tmi.2021.3060066
|View full text |Cite
|
Sign up to set email alerts
|

Learning Inductive Attention Guidance for Partially Supervised Pancreatic Ductal Adenocarcinoma Prediction

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is the third most common cause of cancer death in the United States. Predicting tumors like PDACs (including both classification and segmentation) from medical images by deep learning is becoming a growing trend, but usually a large number of annotated data are required for training, which is very labor-intensive and time-consuming. In this paper, we consider a partially supervised setting, where cheap imagelevel annotations are provided for all the training data, and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Previous studies have employed deep CNNs for automatic PDAC detection on CT scans [ 12 , 13 , 14 , 15 , 16 , 17 ], but only two studies validated their models on an external test set [ 15 , 16 ], with one using the publicly available pancreas dataset. Liu and Wu et al [ 15 ] developed a 2D, patch-based deep learning model using the VGG architecture to distinguish pancreatic cancer tissue from non-cancerous pancreatic tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have employed deep CNNs for automatic PDAC detection on CT scans [ 12 , 13 , 14 , 15 , 16 , 17 ], but only two studies validated their models on an external test set [ 15 , 16 ], with one using the publicly available pancreas dataset. Liu and Wu et al [ 15 ] developed a 2D, patch-based deep learning model using the VGG architecture to distinguish pancreatic cancer tissue from non-cancerous pancreatic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, deep learning models have started to be investigated for automatic PDAC diagnosis [ 12 , 13 , 14 , 15 , 16 , 17 ]. However, most studies perform only binary classification of the input image as cancerous or not cancerous, without simultaneous lesion localization.…”
Section: Introductionmentioning
confidence: 99%
“…Only three articles stratified the results based on tumour size, reporting model performance for the subgroup of lesions with sizes smaller than 2 cm [ 35 , 36 , 37 ]. Two papers (Alves et al (2022) and Wang et al (2021)) reported the results for both lesion detection and localization, and only one paper proposed a fully automatic approach (Alves et al (2022)) [ 35 , 38 ]. The study by Liu et al (2020) was the only one comparing AI performance to radiologists based on the analysis of radiology reports, but no reader study was conducted [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eleven articles addressed AI for automated PDAC detection (Table 1). Only three articles stratified the results based on tumour size, reporting model performance for the subgroup of lesions with sizes smaller than 2 cm [35][36][37] 2022)) [35,38]. The study by Liu et al (2020) was the only one comparing AI performance to radiologists based on the analysis of radiology reports, but no reader study was conducted [37].…”
Section: Detectionmentioning
confidence: 99%
“…In this study, the state-of-the-art, self-configuring framework for medical segmenta- CT scans [12][13][14][15][16][17], but only two studies validated their models on an external test set 218 [15,16], with one using the publicly available pancreas dataset. Liu and Wu, et al More recently, Si, et al [16]…”
mentioning
confidence: 99%